2019
DOI: 10.4054/demres.2019.40.55
|View full text |Cite
|
Sign up to set email alerts
|

The educational gradient of living alone: A comparison among the working-age population in Europe

Abstract: BACKGROUND In recent decades, the proportion of individuals in Western countries living in a oneperson household has increased. Previous research has mainly focused on the increase among the elderly and younger segments of the population, and there is a lack of research regarding the characteristics of individuals living alone among the workingage population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…The descriptive statistics (Table 1) reveal some interesting differences across partnership statuses. We find an overrepresentation of women among the singles in line with previous research (Sandström & Karlsson, 2019), which is explained primarily by women’s lower rates of re-partnering after a breakup or the death of a partner (Bernhardt & Goldscheider, 2002). Co-residents show a more youthful age pattern than individuals in other living arrangements, whereas the truly single have their highest share at ages of 60 years old and above compared to those in partnerships.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The descriptive statistics (Table 1) reveal some interesting differences across partnership statuses. We find an overrepresentation of women among the singles in line with previous research (Sandström & Karlsson, 2019), which is explained primarily by women’s lower rates of re-partnering after a breakup or the death of a partner (Bernhardt & Goldscheider, 2002). Co-residents show a more youthful age pattern than individuals in other living arrangements, whereas the truly single have their highest share at ages of 60 years old and above compared to those in partnerships.…”
Section: Resultssupporting
confidence: 90%
“…Limited SES differences in terms of education across living arrangements in Sweden may be explained by a relatively generous welfare system, limited social inequalities, and widely accepted post-materialistic values (Oláh & Bernhardt, 2008). Labor market attachment mattered only in terms of LAT individuals being less likely to not work for pay than the truly partnerless, due to a selection of the most disadvantaged primarily going into the latter living arrangement (Sandström & Karlsson, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From previous studies, we expected that age, college education, employment status, and ethnicity are all associated with the propensity to live in one-person households (Dommaraju 2015;Guilmoto and de Loenzien 2015;Raymo 2015;Park and Choi 2015;Podhisita and Xenos 2015). The literature suggests that college education and employment are positively associated with independent living arrangements (Sandstrom and Karlsson 2019;Stone, Berrington, and Falkingham 2011;Vitali 2010) due to a higher level of acceptance of individualism and access to the resources needed to live independently. We controlled for ethnicity on the basis that people with Han ethnicity (comprising the ethnic majority in China) may be more likely to live alone than those from ethnic minorities.…”
Section: H4cmentioning
confidence: 95%
“…At the same time, it was a valuable resource as human capital. Previous research have shown substantive differences in partnering, fertility, and other demographic behaviors across educational levels (Dronkers & Härkönen, 2008;Hoem, 1997;Jalovaara et al, 2021;Kalmijn, 2013;Perelli-Harris et al, 2010;Sandström & Karlsson, 2019;Testa & Stephany, 2017;Van Bavel, 2014;Wood et al, 2014).…”
Section: Analytical Strategymentioning
confidence: 97%